SURVEY TINGKAT PENGETAHUAN SISWA TERHADAP MATERI ATLETIK DI SMA NEGERI 1 DARUI IMARAH TAHUN AJARAN 2023/2024 - Maulana, Akhyar; Boihaqi, Boihaqi; Azwar, Edi (Jurnal Seramoe Education, 2024)
This research is entitled "Surve of Students' Level of Knowledge Regarding Athletic Materials at SMA Negeri 1 Darui Imarah Academic Year 2023/2024. The population in this study were students of SMA Negeri 1 Darul Imarah who were in class There are 36 male and female students at SMA Negeri 1 Darul Imarah. As for the research results, based on the research results, it can be concluded that the level of knowledge about athletics material in general is quite high. The majority of students have a good understanding of athletics as a physical activity involving various sports, the importance of athletics in the history of human development, as well as an understanding of the basic techniques and infrastructure used in athletics. However, there are several areas that require more attention, such as understanding the events of running, jumping and throwing which require a combination of strength, technique and coordination. Overall, despite some shortcomings students demonstrated a good knowledge of important aspects of athletics.